Higher levels of matrix metalloproteinase-3 in patients with RA reflect disease activity and structural damage - Skacelova, Martina; Hermanova, Zuzana; Horak, Pavel; Ahmed, Kazi; Langova, Katerina (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2017)
AIMS: To evaluate the serum levels of matrix metalloproteinase-3 (MMP-3) as a potential marker of disease activity and joint damage in 92 patients with rheumatoid arthritis (RA), compared to 24 osteoarthritis (OA) patients and 26 healthy controls. METHODS: The concentrations of MMP-3 were measured by ELISA using the commercial kit AESKULISA DF MMP-3 (AESKU.Diagnostics, Germany) and compared with other laboratory parameters routinely used to assess the disease status, clinical score (DAS28) and radiographic stage in the group of RA patients. RESULTS: The mean serum concentrations of MMP-3 were 199.1 ± 160 ng/mL in RA patients, 113.9 ± 96.9 ng/mL in OA patients and 48.3 ± 19.2 in healthy controls. The differences were highly significant: RA patients and healthy controls (P<0.0001), RA and OA patients (P=0.008) as well as between OA patients and controls (P=0.009). MMP-3 concentrations were further compared with other laboratory parameters and clinical and structural damage data. There were correlations between MMP-3 and CRP (r=0.304, P<0.01), DAS28 (r=0.301, P<0.05), levels of anti-cyclic citrullinated peptide antibodies (r=0.241, P<0.05), erythrocyte sedimentation rate (r=0.200, P=0.059) and radiographic disease stage (r=0.197, P=0.063). CONCLUSION: These results demonstrated that measurement of MMP-3 could become a marker of disease activity in RA patients.
Keywords: matrixová metaloproteinasa 3; Radiography; Disease Progression; biologické markery; revmatoidní faktor; Arthritis, Rheumatoid; lidé středního věku; radiografie; Rheumatoid Factor; lidé; revmatoidní artritida; Middle Aged; Predictive Value of Tests; Enzyme-Linked Immunosorbent Assay; Female; průřezové studie; ELISA; osteoartróza; Biomarkers; Male; ženské pohlaví; Cross-Sectional Studies; progrese nemoci; matrix metalloproteinase-3; Humans; mužské pohlaví; rheumatoid arthritis; Osteoarthritis; Matrix Metalloproteinase 3; prediktivní hodnota testů; krevní sedimentace; disease activity; Blood Sedimentation